2004
DOI: 10.1534/genetics.104.026831
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Disequilibrium Mapping of Yield and Yield Stability in Modern Spring Barley Cultivars

Abstract: Associations between markers and complex quantitative traits were investigated in a collection of 146 modern two-row spring barley cultivars, representing the current commercial germ plasm in Europe. Using 236 AFLP markers, associations between markers were found for markers as far apart as 10 cM. Subsequently, for the 146 cultivars the complex traits mean yield, adaptability (Finlay-Wilkinson slope), and stability (deviations from regression) were estimated from the analysis of variety trial data. Regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
305
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(329 citation statements)
references
References 51 publications
19
305
4
Order By: Relevance
“…A total of 148 modern European two-row spring barley cultivars were used, representing commercial germplasm used all over north-west Europe in the past 15 years (see Kraakman et al 2004 for more details). The list of cultivars and the breeding companies that bred them are presented as supplementary data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 148 modern European two-row spring barley cultivars were used, representing commercial germplasm used all over north-west Europe in the past 15 years (see Kraakman et al 2004 for more details). The list of cultivars and the breeding companies that bred them are presented as supplementary data.…”
Section: Methodsmentioning
confidence: 99%
“…In sugar beet, LD extended up to 3 cM (Kraft et al 2000), while in some Arabidopsis populations LD exceeded even 50 cM (Nordborg et al 2002). Kraakman et al (2004) showed that in a set of 148 modern spring barley cultivars markers at distances up to 10 cM tend to be in LD (see their Figure 2). …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Through detecting abundant genetic markers loci locating in genome or those nearby candidate genes, the loci which link tightly with QTLs and show correlated to QTLs can be found. The application of association mapping to plant breeding appears to be a promising approach to overcome the limitations of conventional linkage mapping (Kraakman et al, 2004).…”
Section: Association Mapping With the Rice Core Collectionmentioning
confidence: 99%
“…Moreover, association mapping can detect the majority of loci controlling the same complex traits and multiple alleles of the same locus. Association mapping was first used to detect alleles in human disease and has now been widely applied to gene mapping in plants [14][15][16][17][18][19][20][21].…”
mentioning
confidence: 99%